All-graphene perfect broadband THz absorber. (15th November 2021) - Baah, Marian; Paddubskaya, Alesia; Novitsky, Andrey; Valynets, Nadzeya; Kumar, Mukesh; Itkonen, Tommi; Pekkarinen, Markku; Soboleva, Ekaterina; Lahderanta, Erkki; Kafesaki, Maria; Svirko, Yuri; Kuzhir, Polina
Abstract: By combining the 3D printing, electroplating and chemical vapor deposition processes we fabricated "bubble wrap" polymer nanomembrane covered with multilayered graphene. Such a metasurface composed of array of graphene hemispheres shows extremely broadband and almost perfect absorption in terahertz (THz) 2 frequency range being robust against macroscopic structural defects including holes and volcanic-like hats on hemispherical metaatoms. The developed theory perfectly explains our experimental findings including virtual independence of the metasurface transmittivity, reflectivity and absorptivity on the angle of incidence in terms of the plasmon dark mode formation. Our approach enables the THz perfect absorber that covers a frequency range spanning from few hundreds of GHz to 1.2 THz, and even more, while the proposed fabrication technique can also be employed in numerous applications that require free standing corrugated graphene/polymer nanomembranes. Graphical abstract: Image 1 Highlights: Free standing multilayered graphene membrane was fabricated by 3D printing, electroplating and chemical vapor deposition. This technique can be employed in applications requiring free standing corrugated graphene/polymer membranes. A metasurface composed of graphene array of hemispheres shows broadband perfect absorption at terahertz frequencies. Perfect absorption is robust against macroscopic structural defects: holes, volcanic-like hats on hemispherical metaatoms. The independence of metasurface absorptance on the radiation incidence angle is explained in terms of the plasmon dark mode.